Impact of Pandemic Covid-19 On Human Resources Management - Ismail, Fadillah (Advances in Humanities and Contemporary Studies, 2021)
The COVID-19 pandemic that has hit the world, including Malaysia, is a health crisis that threatens the survival, well-being of society and affect Human Resource practices. In February 2020, the Malaysian Employers Federation (MEF) has estimated that 100,000 workers will be laid off, if the transmission of the COVID-19 virus continues until the end of 2020.However, the assumption is refuted by the Ministry of Human Resources (KSM) because it is speculative and does not take into account the various initiatives that have been and will be implemented by the Government and as well as being a commitment and responsibility of human resource management in ensuring the welfare of employees to given priority and protect the interests of workers. Therefore, this paper aims to examines the effects and consequences of the pandemic Covid19 on human resource management in ensuring industrial harmony.